Anti-proliferative, genotoxic and cytotoxic effects of phytochemicals isolated from Anatolian medicinal plants - Kasapoğlu, Kadriye Nur; Altin, Gokce; Farooqi, Ammad Ahmad; Salehi, Bahare; í–zçelik, Beraat; Setzer, William N.; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2020)
The potential of natural products in cancer prevention and treatment has received worldwide interest in recent years from the nutraceutical and pharmaceutical industry point of view. Medicinal plants have been traditionally used as they exhibit a wide range of therapeutic effects due to their phytoconstituents which play an active role against oxidative stress-associated diseases such as cancer. They may block or suppress multistage carcinogenesis mainly through mechanistic regulation of the myriad of deregulated cellular pathways. Bioactive constituents isolated from different plants have been shown to induce reversal of drug resistance, restoration of apoptosis, inhibition of cell proliferation and stimulation of the immune system, etc. These phytochemicals such as terpenoids, flavonoids, phenolic acids, carotenoids, alkaloids, tannins, anthraquinones, and saponins can be present in any of the plant parts like root, stem, leaves, bark, seed, flower, and fruit which produce a definite physiological response in the organism. Turkish flora is a rich reservoir of wide-ranging bioactive chemicals having premium pharmacological importance. This review provides an overview of the anticancer properties of various Turkish medicinal plant species against different type of cancers via anti-proliferative, genotoxic and cytotoxic effects.